Nanomaterial-based aptamer sensors for arsenic detection - Mao, Kang; Zhang, Hua; Wang, Zhenglu; Cao, Haorui; Zhang, Kuankuan; Li, Xiqing; Yang, Zhugen (Elsevier, 2019)
Arsenic (As) is a highly toxic contaminant in the environment and a serious carcinogen for the human being. The toxicity of arsenic significantly threatens environmental and human health. The effective removing technology for arsenic remains challenging, and one of the reasons is due to the lack of powerful detection method in the complex environmental matrix. There is thus an urgent need to develop novel analytical methods for arsenic, preferably with the potential for the field-testing. To combat arsenic pollution and maintain a healthy environment and eco-system, many advanced analytical methods have been developed for arsenic detection in various samples. Among these strategies, biosensors hold great promise for rapid detection of arsenic, in particular, nanomaterials-based aptamer sensors have attracted significant attention due to their simplicity, high sensitivity and rapidness. In this paper, we reviewed the recent development and promising applications of aptamer sensors (aptasensors) based-on nanomaterial for arsenic detection, in particular with emphasis on the works using optical and electrochemical technologies. We also discussed the recent novel technology in aptasensors development for arsenic detection, including nucleic acid amplification for signal enhancement and device integration for the portability of arsenic sensors. We are hoping this review could inspire further researches in developing novel nanotechnologies based aptasensors for possible on-site detection of arsenic.
Keywords: Arsenic; Aptasensors; Nanomaterials; Optical and electrochemical sensors; Signal amplification